Formation of the network society and the issues of cybersecurity - Сопілко, Ірина Миколаївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2016)
Today, there are threats to the territorial integrity and security of Ukraine, and information security is one of the essential components of national security. Accordingly, holding of a successful information policy, by the state and civil society, can significantly affect the resolution of domestic, foreign and military conflicts and bring Ukraine closer to international standards in information security and overall security. The main space for information is a developed information society, one of the elements of which is the network society. The purpose of this article - to identify the main threats to the network society in the context of information security. The current state of national and information security of Ukraine needs to develop science-based public policy and strategy to prevent abuse of information and to protect information rights, to determine the national values and vital interests of the individual, society and state, to define the internal and external threats to those interests , to find effective measures to ensure security in all its areas of protection against information threats and the right to obtain reliable information. There is a need in the adoption of regulations which would have provided a mechanism of protection of information rights of citizens against unlawful acts of third parties for information and limit its impact on a person in connection with the use of appropriate information networks. There is a particular relevance in improving of the software of the main state institutions, organizations and enterprises. It is also necessary to improve the system of counteraction to information attacks using social networks.